Consuming the non-human and the less-than-human: A critical study of Sarah Kane’s Blasted (1995) - Singh, Maninder; Bhattacharya, Suchismita (Research Journal in Advanced Humanities, 2023)
The epoch of the Anthropocene, with accelerating technological advances and growing economic and social inequalities, have made the spatial reality more violent, intolerable, discriminatory and disintegrating. These growing inequalities set the conditions for exploitation and subjugation. While the privileged section of the human population buys their way out and lives comfortably within the closed spaces of their gated communities amidst the global devastation; the underprivileged, on the other hand, have to confront the consequences. Within the privileged closed space, the food is available in abundance, and is lavishly served, consumed and even wasted; but for those outside the privileged closed space, the scarcity and unavailability of food is an imminent threat. The paper focuses on the fragility of the economy of food within the gradually worsening Anthropocene condition, especially the over-dependence of global food supply chains. The paper places Sarah Kane’s play Blasted (1995) in one such condition, such as conflict or war, in which the food supply is halted and the havoc is unleashed. In Blasted, the object of consumption, the food eaten by human subjects when the food supply chains are unharmed, is the non-human flora and fauna. And when the food supply chains are disrupted or halted, when the bubble of a safe closed space bursts and when the food is hard to come by, the natural instinct to survive kicks in and the human subjects do everything in their power to survive, including cannibalizing the less-that-human or the dehumanized Other.